Anthropomorphic finger with optimized geometric parameters for pinching and grasping tasks - Zainul Azlan, Norsinnira; Yamaura, Hiroshi (Elsevier B.V., 2012)
This paper presents the parameter optimization procedure for a new anthropomorphic finger mechanism in performing pinching and self-adaptive grasping operation. The mechanism is made based on the observation of human finger during grasping and pinching. It is constructed from seven bar linkages and its upper middle phalanx is incorporated with a curved guiding slot and lead screw mechanism to adjust the link's effective length in accomplishing these two tasks. The finger's geometrical parameters are optimized based on four design criteria, which are the anthropomorphic pinching kinematics and force; and grasping kinematics and force to enhance its performance. The numerical result obtained gives an improved parameter set compared to the initial guess. A prototype with small size and light weight actuators and sensors has been implemented based on the optimum solution to achieve a compact anthropomorphic design with grasping and pinching capabilities.